Rehabilitation Perspectives in Long COVID-19 - Farooq Azam Rathore; Muhammad Tawab Khalil; Omer Jamshed Khan (Journal of the Pakistan Medical Association, 2023)
Long COVID is a term used to describe the persistence of symptoms in people who have had COVID-19 for an extended period. It affects multiple systems including neurological (fatigue, brain fog, attention issues, memory issues), neuromuscular (sarcopenia, myositis, arthritis and myopathy), cardiovascular (myopericarditis, right ventricular dysfunction, vasculitis and aortic, arterial and venous thrombosis) and respiratory (pulmonary fibrosis, pleurisy, pulmonary embolism and pneumonitis). This results in functional impairments which adversely affect the quality of life of patients. The rehabilitation of persons who have experienced long COVID-19, also known as "long haulers," is a relatively new field of study. We have described potential rehabilitation interventions to improve functional capacity and quality of life in patients with long COVID. These rehabilitation interventions include but are not limited to, endurance, flexibility and strength training, pulmonary rehabilitation, task specific exercises to improve Activities of Daily Living (ADL), psychological rehabilitation, medical rehabilitation, pain management and management of dysphagia. Keywords: Long haulers; Chronic COVID; aerobic training; cognitive behavioural therapy; activities of daily living; rehabilitation